Foreign Aid and State Legitimacy: Evidence on Chinese and US Aid to Africa from Surveys, Survey Experiments, and Behavioral Games. (16th April 2021) - Blair, Robert A.; Roessler, Philip
ABSTRACT: What are the effects of foreign aid on the perceived legitimacy of recipient states? Different donors adhere to different rules, principles, and operating procedures. The authors theorize that variation in these aid regimes may generate variation in the effects of aid on state legitimacy. To test their theory, they compare aid from the United States to aid from China, its most prominent geopolitical rival. Their research design combines within-country analysis of original surveys, survey experiments, and behavioral games in Liberia with cross-country analysis of existing administrative and Afrobarometer data from six African countries. They exploit multiple proxies for state legitimacy, but focus in particular on tax compliance and morale. Contrary to expectations, the authors find little evidence to suggest that exposure to aid diminishes the legitimacy of African states. If anything, the opposite appears to be true. Their results are consistent across multiple settings, multiple levels of analysis, and multiple measurement and identification strategies, and are unlikely to be artifacts of sample selection, statistical power, or the strength or weakness of particular experimental treatments. The authors conclude that the effects of aid on state legitimacy at the microlevel are largely benign.